Risk stratification by combining common genetic mutations and TERT promoter methylation in papillary thyroid cancer - Sang, Ye; Hu, Guanghui; Xue, Junyu; Chen, Mengke; Hong, Shubin; Liu, Rengyun (Endocrine, 2024)
Purpose Risk stratification based on somatic mutations in TERT promoter and BRAF / RAS has been well established for papillary thyroid cancer (PTC), and there is emerging evidence showed that TERT promoter methylation was frequently observed in thyroid cancer patients with adverse features. This study was aimed to comprehensive explore the prognostic value of BRAF / RAS mutations, TERT promoter mutations, and TERT promoter methylation in PTC. Methods The relationships of BRAF / RAS mutations, TERT promoter mutations, and TERT promoter methylation with clinical characteristics and outcomes of PTC were analyzed in 382 patients with PTC. Results TERT promoter mutation and hypermethylation were collectively observed in 52 (13.6%) samples and associated with BRAF / RAS mutation, aggressive clinical characteristics, and poor clinical outcomes of PTC. Coexistence of BRAF / RAS and TERT alterations was found in 45 of 382 (11.8%) PTC patients and strongly associated with old patient age, extrathyroidal extension, advanced pathologic T stage and metastasis. Importantly, patients with both BRAF / RAS and TERT alterations had higher rates of tumor recurrence (13.6% vs 1.5%, P = 0.042) and disease progression (24.4% vs 3.3%, P < 0.001) than patients without any alterations, and cox regression analysis revealed that the coexistence of BRAF / RAS and TERT alterations, but not BRAF / RAS or TERT alterations alone, increased the risk of progression-free interval with an adjusted HR of 10.35 (95% CI: 1.79–59.81, P = 0.009). Conclusions This study suggested that comprehensively analysis of BRAF / RAS mutations, TERT promoter mutation and methylation is an effective strategy to identify high-risk patients with PTC.